Reflective optics - Korsch, Dietrich (Academic Press, 1991)
This is the first book dedicated exclusively to all-reflective imaging systems. It is a teaching tool as well as a practical design tool for anyone who specializes in optics, particularly for those interested in telescopes, infrared, and grazing-incidence systems. The first part of the book describes a unified geometric optical theory of all-reflective imaging systems (from near-normal to grazing incidence) developed from basic principles. The second part discusses correction methods and a multitude of closed-form solutions of well-corrected systems, supplemented with many conventional and unconventional designs examples. This book will be useful to anyone interested in the theory of optical image formation and in the actual design of image-forming instruments.